#Menopause on Instagram: a mixed-methods study. Issue 4 (April 2021) - Arseneau, Morgan E.; Backonja, Uba; Litchman, Michelle L.; Karimanfard, Rojin; Sheng, Xiaoming; Taylor-Swanson, Lisa
Abstract: Objective: The aims of this study were to: (1) characterize the menopause transition (MT) on social media and (2) determine if concordance or discordance exists when comparing MT-focused social media posts and biomedical research literature. Methods: We analyzed 440 sequential Instagram posts with the hashtag #menopause over 2 weeks from January to February 2019. Posts were composed of 299 unique accounts, resulting in an average of 1.7 posts per account (standard deviation [SD] 1; range 1-9; median 1 and interquartile range [IQR] 1-2). Each account had an average of 2, 616 followers (SD 11, 271; range 3-129, 000; median 421.5 and IQR 177-1, 101). Content and thematic analyses were completed for posts, images, and videos to identify codes related to the MT. The top 15 codes were then searched along with the key term "menopause" in PubMed to ascertain the level of concordance between Instagram content and peer-reviewed literature on the MT. Results: We identified 69 codes in our corpus of Instagram content, resulting in 9 categories: physical health, mental health, complementary and integrative health, advertising, social, advice, self-care, nature, and self-expression (kappa 0.95-1.00). The most prevalent codes were related to weight loss/fitness (20.5%) and hormones (18.4%). The majority of frequent codes identified in Instagram posts were infrequently listed in biomedical literature related to menopause. However, there were two codes, Weight loss/Fitness and Hot flashes, that were frequently discussed in Instagram posts and the biomedical literature. Conclusions: The examination of #menopause on Instagram provides novel insights for researchers and clinicians. Our findings provide a better understanding of the experiences and support needs of individuals experiencing menopause. Furthermore, codes related to menopause have low prominence in the biomedical literature, suggesting key topics that could be explored in the future. N/A: Video Summary: http://links.lww.com/MENO/A695 . Abstract : Supplemental Digital Content is available in the text